Clinical Outcomes of Patients With Gastric Phytobezoars: Implication of Drinking Carbonated Beverages as a Treatment - Jin Ook Jang; Cheol Woong Choi; Dae Gon Ryu; Su Bum Park; Su Jin Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Objectives Although phytobezoars are the most common type of gastric bezoar, a standardized treatment method has not been adopted. Methods In this study, we evaluated patient clinical features and treatment outcomes following the use of different treatment methods, with a focus on the efficacy of carbonated beverage consumption. A review of medical charts and endoscopic reports revealed 15 cases of gastric phytobezoars from September 2008 to May 2016. Patient medical records were retrospectively reviewed to assess patient clinical characteristics and treatment results. Results The mean patient age was 71.3±11.1 years. The most common symptoms were epigastric pain (46.7%) and bloating (40.0%). A history of intra-abdominal surgery was found in 26.7% of the patients. The mean bezoar size was 47.3±14.5 mm. The final successful treatment methods were consumption of a carbonated beverage alone (n=7, 46.7%), endoscopic removal (n=5, 33.3%), and surgery (n=3, 20.0%). During the treatment course, few patients (3/15, 20.0%) experienced small bowel obstructions after the consumption of the carbonated beverage and endoscopic fragmentation; these obstructions required surgical interventions. There was no significant difference in the baseline characteristics between patients successfully or unsuccessfully treated with the carbonated beverage. Conclusions Most patients presenting with gastric phytobezoars can be successfully treated by consuming carbonated beverages in conjunction with endoscopic therapy. However, small bowel obstructions may occur due to the migration of a fragmented bezoar, necessitating surgical intervention.